U–Pb zircon geochronology of the North Pole Dome adamellite in the eastern Pilbara Craton. (26th April 2018) - Asanuma, Hisashi; Sawaki, Yusuke; Sakata, Shuhei; Obayashi, Hideyuki; Suzuki, Kazue; Kitajima, Kouki; Hirata, Takafumi; Maruyama, Shigenori
Abstract: Supracrustal rocks around the North Pole Dome area, Western Australia, provide valuable information regarding early records of the evolution of crustal processes, surface environments, and biosphere. Owing to the occurrence of the oldest known microfossils, the successions at the North Pole Dome area have attracted interest from many researchers. The Paleoarchean successions (Warrawoona Group) mainly comprise mafic‐ultramafic greenstones with intercalated cherts and felsic lavas. Age constraints on the sediments have been mainly based on zircon U–Pb geochronology. However, many zircon grains have suffered from metamictization and contain anomalously high contents of common Pb, which makes interpretation of the U–Pb data complicated. In order to provide more convincing chronological constraints, an U–Pb Concordia age is widely accepted as the best estimate. Most zircons separated from two adamellites also suffered from severe metamictization. In our analyses, less metamictized domains were selected using a pre‐ablation technique in conjunction with elemental mapping, and then their U–Pb isotopic compositions were determined with a laser ablation inductively coupled plasma mass spectrometry. Most analyzed domains contained certain amounts of common Pb ( 204 Pb/ 206 Pb > 0.000 1), whereas three and five U–Pb data points with less common Pb ( 204 Pb/ 206 Pb < 0.000 1) were obtained. These U–Pb datasets yielded U–Pb Concordia ages of ca 3 445 Ma and 3 454 Ma, respectively. These ages represent the timing of the adamellite intrusion, and constrain the minimum depositional age of the Warrawoona Group. In addition, a single xenocrystic zircon grain showed a 207 Pb/ 206 Pb age of ca 3 545 Ma, supporting the idea that the sialic basement of the Pilbara Craton existed prior to 3 500 Ma. The in situ U–Pb zircon dating combined with the pre‐ablation technique has the potentials to identify non‐metamictized parts and to yield precise and accurate geochronological data even from partially metamictized zircons. Abstract : Our study first reports the U–Pb Concordia ages of 3 445 and 3 454 Ma from the North Pole Dome adamellite in the eastern Pilbara Craton. These intrusive ages are available as the minimum age constraint of the North Pole Dome successions, and provide important clues about re‐interpretation of their geochronology and stratigraphy.